Multiple Soft Tissue Sarcomas in a Single Patient: An International Multicentre Review. (1st April 2018) - Lex, Johnathan R.; Aoude, Ahmed; Stevenson, Jonathan D.; Wunder, Jay S.; Evans, Scott; Ferguson, Peter C.; Stavropoulos, Nikolaos A.; Jeys, Lee; Goulding, Krista; Turcotte, Robert E.
Abstract : Developing multiple soft tissue sarcomas (STSs) is a rare process, sparsely reported in the literature to date. Little is known about the pattern of disease development or outcomes in these patients. Patients were identified from three tertiary orthopaedic oncology centres in Canada and the UK. Patients who developed multiple extremity STSs were collated retrospectively from prospective oncology databases. A literature review using MEDLINE was also performed. Six patients were identified in the case series from these three institutions, and five studies were identified from the literature review. Overall, 17 patients were identified with a median age of 51 years (range: 19 to 77). The prevalence of this manifestation in STS patients is 1 in 1225. The median disease-free interval between diagnoses was 2.3 years (range: 0 to 19 years). Most patients developed the secondary STS in a metachronous pattern, the remaining, synchronously. The median survival after the first sarcoma was 6 years, and it was 1.6 years after the second sarcoma. The 5-year overall survival rate was 83.3% and 50% following the first and second STS diagnoses, respectively. A diagnosis of two STSs does not confer a worse prognosis than the diagnosis of a single STS. Developing a second STS is a rare event with no identifiable histological pattern of occurrence. Presentation in a metachronous pattern is more common. A high degree of vigilance is required in patients with a previous STS both to detect both local recurrence and to identify new masses remote from the previous STS site. Acquiring an early histological diagnosis should be attempted.